Evaluation of acetic acid treatment of fresh–cut water chestnuts using gray–correlation analysis based on the variation–coefficient weight - Zhang, Yongqing; Li, Haiyan; Liu, Jiangfan; Wei, Quanzeng; Sun, Juntao; Wang, Deguo (Frontiers in Nutrition, 2024)
The demand for fresh-cut water chestnuts, a convenient and nutritive vegetable, is increasing in market. However, the slicing of water chestnuts can cause mechanical damage to tissue, which results in quality deterioration. We aimed to select the optimal treatment through a comprehensive comparison of the preservation effect of acetic acid, which could prolong the shelf life of fresh-cut water chestnuts and improve their storage quality.Methods: A comprehensive evaluation was conducted using the grey-correlation method based on the variation-coefficient weight to observe the treatment of 0, 2% and 5% acetic acid. Their effects on color, weight loss rate, and the content of ascorbic acid, total sugar, reducing sugar, soluble protein, and free amino acid were determined.The color, weight loss rate, and nutritional content of fresh-cut chestnuts varied under different processing and storage times. When stored for more than 4 days, the b * value, and the content of total sugar and soluble protein in CK were higher than those in 2% or 5% acetic acid, but the weight loss rate, and the content of ascorbic acid and free amino acid in CK were less than those in acetic acid treatments. Considering various indicators, it was difficult to determine which treatment to choose for fresh-cut water chestnut preservation. The grey-correlation analysis results indicated that when stored for 8, 12, or 16 days, the grey-correlation degree of 5% acetic acid was the highest, while that of the control was the lowest. It could be directly concluded by the greycorrelation degree that when the storage time exceeded 4 days, acetic acid could be used to improve storage quality, and 5% acetic acid had a better preservation effect than 2%. Fresh-cut water chestnuts can be stored for 4 days without the need for acetic acid treatment.These findings could provide information and comprehensive evaluation methods for the preservation of fresh-cut fruits and vegetables. The next step is to evaluate the preservation effect of acetic acid by measuring its effects on other indicators of fresh-cut water chestnuts (e.g., flavonoids, and microorganisms), providing ideas for the research of preservatives.